Social Development, Change, and Progress - Midgley, James (Social development issues, 2024)
The following article is a revised version of the 2021 Khinduka Lecture given at the 22nd Biennial Meeting of the International Consortium for Social Development (ICSD) held in Johannesburg, South Africa in July 2021. The lecture discusses the concepts of change and progress, which have played a prominent role in social development thinking over the years. It reviews some of the changes that have taken place during Professor Khinduka’s lifetime, noting that there have been huge shifts in geopolitics, economics, living standards, attitudes, communications, and science and technology. It then asks whether these changes have brought real progress to the world’s people and considers different views on the subject by leading thinkers. In contrast to the views of those who take a pessimistic view with those who have reached optimistic conclusions, it suggests that the situation is mixed, with progress being recorded in some fields but not in others. It concludes by asking how social development advocates can bring about progressive change and progress.